2018
DOI: 10.3892/mmr.2018.8642
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane reduces pain and inhibits apoptosis of myocardial cells through the phosphoinositide 3-kinase/protein kinase�B signaling pathway in mice during cardiac surgery

Abstract: Heart bypass surgery is the most common treatment for myocardial ischemia. Clinical investigations have revealed that isoflurane anesthesia is efficient to alleviate pain during cardiac surgery, including heart bypass surgery. Previous studies have revealed the protective effects of isoflurane on myocardial cells of patients with myocardial ischemia during the perioperative period. The present study aimed to investigate the mechanism underlying the protective effects of isoflurane on myocardial cells in mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…To further test this idea, we injected NMDA into eyes of Thy1-GFP mice, in which most, if not all, RGCs are GFP-expressing, and labeled NMDA-treated retinas using an anti-CASP3 antibody to identify cells undergoing apoptosis ( Pi et al, 2018 ). The results show that some GFP-positive cells are also CASP3-positive 3 h after NMDA injection ( Figure 2H ), indicating that RGCs actively undergoing apoptosis are still GFP positive, while no CASP3-positive RGCs are found in non-injected eyes (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…To further test this idea, we injected NMDA into eyes of Thy1-GFP mice, in which most, if not all, RGCs are GFP-expressing, and labeled NMDA-treated retinas using an anti-CASP3 antibody to identify cells undergoing apoptosis ( Pi et al, 2018 ). The results show that some GFP-positive cells are also CASP3-positive 3 h after NMDA injection ( Figure 2H ), indicating that RGCs actively undergoing apoptosis are still GFP positive, while no CASP3-positive RGCs are found in non-injected eyes (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Isoflurane, a general inhalation anesthetic used for the induction and maintenance of general anesthesia, promotes PI3K/AKT activation, upregulates B-cell lymphoma 2 (Bcl-2)-associated X protein Bcl-2 expression levels, and reduces the expression levels of caspase 3 and caspase 8 in myocardial cells. Isoflurane is beneficial for pain attenuation and inhibits apoptosis in myocardial cells via the PI3K/AKT signaling pathway in mice during cardiac surgery [ 132 ]. Further, Masahiko Kawaguchi et al (2004) showed that isoflurane reduced the early development of neuronal apoptosis in rats subjected to focal cerebral ischemia [ 133 ].…”
Section: Apoptosis and Clinical Implicationsmentioning
confidence: 99%
“…Although anesthetics are widely used during a range of procedures, their exact mechanism, and overall outcomes are still not completely understood. Some studies have suggested that isoflurane has some anti-cell death properties [41][42][43]. Ketamine is reported to reduce brain injury by inhibiting apoptosis [11,44,45] and exerting anti-inflammatory effects [6,46].…”
Section: Discussionmentioning
confidence: 99%